A Therapeutic Nanovaccine that Generates Anti‐Amyloid Antibodies and Amyloid‐specific Regulatory T Cells for Alzheimer's Disease. Issue 3 (19th December 2022) - Jung, Mungyo; Lee, Songmin; Park, Sohui; Hong, Jihye; Kim, Cheesue; Cho, Illhwan; Sohn, Hee Su; Kim, Kyunghwan; Park, In Wook; Yoon, Soljee; Kwon, Sungpil; Shin, Jisu; et al.
Abstract: Alzheimer's disease (AD), the most common cause of dementia, is a complex condition characterized by multiple pathophysiological mechanisms including amyloid‐β (Aβ) plaque accumulation and neuroinflammation in the brain. The current immunotherapy approaches, such as anti‐Aβ monoclonal antibody (mAb) therapy, Aβ vaccines, and adoptive regulatory T (Treg) cell transfer, target a single pathophysiological mechanism, which may lead to unsatisfactory therapeutic efficacy. Furthermore, Aβ vaccines often induce T helper 1 (Th1) cell‐mediated inflammatory responses. Here, a nanovaccine composed of lipid nanoparticles loaded with Aβ peptides and rapamycin is developed, which targets multiple pathophysiological mechanisms, exhibits the combined effects of anti‐Aβ antibody therapy and adoptive Aβ‐specific Treg cell transfer, and can overcome the limitations of current immunotherapy approaches for AD. The Nanovaccine effectively delivers rapamycin and Aβ peptides to dendritic cells, produces both anti‐Aβ antibodies and Aβ‐specific Treg cells, removes Aβ plaques in the brain, alleviates neuroinflammation, prevents Th1 cell‐mediated excessive immune responses, and inhibits cognitive impairment in mice. The nanovaccine shows higher efficacy in cognitive recovery than an Aβ vaccine. Unlike anti‐Aβ mAb therapy and adoptive Treg cell transfer, both of which require complicated and costly manufacturing processes, the nanovaccine is easy‐to‐prepare and cost‐effective. The nanovaccines can represent a novel treatment option for AD. Abstract : Rapamycin‐incorporated lipid nanoparticle containing amyloid‐β (LNP‐R/Aβ) attenuates neuroinflammation and improves cognitive function in a transgenic rodent model of Alzheimer's disease (AD) by inducing tolerogenic dendritic cells and Aβ‐specific regulatory T cells, and generating anti‐amyloid antibodies. Furthermore, LNP‐R/Aβ reduces T helper 1 cells in AD brains, implying lower risks of meningitis, which is the major reason for the failure of conventional Aβ vaccines.